Leonardo's ink bottle the artist's way of seeing - Weir, Roberta (Berkeley, CA Celestial Arts Publishing, 1998)
"The artist's search for unique, meaningful expression, on paper or canvas, in clay or marble, wood or bronze, is actually mirrored in each of us. Whether we are composing a letter, a song lyric, or a landscape, the desire is the same: to express ourselves easily, elegantly, and eloquently. An artist by vocation and profession, Roberta Weir guides the reader with a steady voice and a sure hand. Part 1 describes the rediscovery of and reliance upon instinct, intuition and inspiration; Part 2 examines the mastery of technique; and Part 3 brings us full circle: having reached a degree of comfort with the nature of inspiration and the mechanics of rendering artistic forms, we are asked to cast it all aside-to stop thinking about it-and just do it."--
Chapter 1 Art: The Seer and the Seen--
Chapter 2 Paradise: The Innocent Eye--
Chapter 3 Beauty: the Eternal Compass--
Chapter 4 Desire: The Divining Rod of Truth--
Chapter 5 Creativity: The Outer Expression of Inner Worlds--
Chapter 6 Reawakening: Opening to the Self--
Chapter 7 Imagination: The Mind's Eye--
Chapter 8 Symbolism: The universal Language--
Chapter 9 Chaos: Leonardo's Ink Bottle--
Chapter 10 Solitude: Alone but not Lonely--
Chapter 11 Courage: Facing a world of Horror--
Chapter 12 Dreaming: Seeing with Eyes Closed--
Chapter 13 Hands: The Human Touch--
Chapter 14 Attention: Observation and Perception:
Chapter 15 Seeing: The Light, the Eye, and the Mind--
Chapter 16 Nudes: Drawing from Life--
Chapter 17 Style: What has Never Been--
Chapter 18 Self: Being Who We Are--
Chapter 19 Expectation: Dismantling Artist's Block--
Chapter 20 Self-Portrait: The Face in The Mirror--
Chapter 21 Action: A Movement of the Mind in Time--
Chapter 22 Nature: The Landscape of Landscape--
Chapter 23 Discipline: Balancing Practice and Spontaneity--
Chapter 24 Education: In the Footsteps of the Masters--
Chapter 25 Consciousness: Horse and Rider--
Chapter 26 Time: Watching the River Flow--
Chapter 27 Meaning: What Does it Mean?--
Chapter 28 Indifference: No Time Like the Present--
Chapter 29 Philosophy: East and West--
Chapter 30 Childhood: The Rediscovery of the World--
Chapter 31 Home: Back to the Stars--
Includes bibliographical references
Keywords: Self-perception.; Artists -- Psychology